2014
DOI: 10.1017/s0266466614000668
|View full text |Cite
|
Sign up to set email alerts
|

Nonparametric Identification of Positive Eigenfunctions

Abstract: Important features of certain economic models may be revealed by studying positive eigenfunctions of appropriately chosen linear operators. Examples include long-run risk-return relationships in dynamic asset pricing models and components of marginal utility in external habit formation models. This paper provides identification conditions for positive eigenfunctions in nonparametric models. Identification is achieved if the operator satisfies two mild positivity conditions and a power compactness condition. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Qin, Linetsky, and Nie (2016) further showed that, under L, the term structure of bond Sharpe ratios for a sufficiently small holding period generally has an increasing shape in the bond maturity T , with the long bond achieving the maximal instantaneous Sharpe ratio under L (the Hansen and Jagannathan (1991) bound). The empirical shape of the term structure of bond Sharpe ratios estimated in Qin, Linetsky, and Nie (2016) is generally opposite to the one described above, indicating that the martingale component in the long-term factorization is highly economically significant, complementing empirical results in Alvarez and Jermann (2005), Bakshi and Chabi-Yo (2012), Borovička, Hansen, and Scheinkman (2016), and Christensen (2016a).…”
Section: The Long-term Limitmentioning
confidence: 59%
See 1 more Smart Citation
“…Qin, Linetsky, and Nie (2016) further showed that, under L, the term structure of bond Sharpe ratios for a sufficiently small holding period generally has an increasing shape in the bond maturity T , with the long bond achieving the maximal instantaneous Sharpe ratio under L (the Hansen and Jagannathan (1991) bound). The empirical shape of the term structure of bond Sharpe ratios estimated in Qin, Linetsky, and Nie (2016) is generally opposite to the one described above, indicating that the martingale component in the long-term factorization is highly economically significant, complementing empirical results in Alvarez and Jermann (2005), Bakshi and Chabi-Yo (2012), Borovička, Hansen, and Scheinkman (2016), and Christensen (2016a).…”
Section: The Long-term Limitmentioning
confidence: 59%
“…This characterization enhances our understanding of risk pricing over alternative investment horizons. The growing related literature includes Hansen (2012), Hansen andScheinkman(2012, 2017), Borovička, Hansen, and Scheinkman (2016), Bakshi and Chabi-Yo (2012), Christensen (2016aChristensen ( , 2016b, , and Qin, Linetsky, and Nie (2016).…”
Section: Introductionmentioning
confidence: 99%
“…This characterization enhances our understanding of risk pricing over alternative investment horizons. The growing related literature includes Hansen (2012), Hansen and Scheinkman (2012), Hansen and Scheinkman (2014), Borovička et al (2016), Bakshi and Chabi-Yo (2012), Christensen (2016a), Christensen (2016b), and .…”
Section: Introductionmentioning
confidence: 99%
“…Under general conditions (see Hansen and Scheinkman (2009) and Christensen (2015Christensen ( , 2017), there exists a strictly positive function ι and scalar λ > 0 solving 9 the equation…”
Section: New Resultsmentioning
confidence: 99%